Remote Learning Strategies for Students With Emotional and Behavioral Disorders. (December 2022) - Heinz, Sarah N.; Andzik, Natalie R.
There is a growing concern among teachers and parents regarding how best to teach children with emotional and behavioral disorders (EBD) in a remote learning format. Students with EBD may have specific needs that present as unique and challenging for teachers to address and when engaging in remote learning. We will discuss research-informed, adapted virtual methods, including strategies to make students feel comfortable socially and academically.